Knowledge And Attitude Towards Menopause In Middle Aged Pakistani Women - Rehana Yasmeen; Rubina Hussain; Shama Chaudhry; Aliya Waheed (ziauddin University, 2024)
Background: Menopause lead to changes in women's physiological functioning. It has significant physical, mental, social and psychological impact on women's life. The purpose of this study was to investigate the knowledge and attitude of middle age women toward the menopause. Methods: A cross sectional study based on sample of convenience was conducted at the outpatient department of Ziauddin Hospital, Karachi from 1st July 2014 to 31st January 2015. The study participants were 250 menopausal women between the ages of 45-60 years. Data was collected by means of a questionnaire, which consists of three parts containing questions about demographic information, knowledge and attitude. Results: The mean age of women in the current study was 51.9 +/- 4.2years (range 45 - 60 years). The mean age at menopause was 45.9 +/- 3.8years. As far as the knowledge about menopause is concerned 4.8% (12women) had weak, 71.2% (178women) had moderate and 24% (60women) had good knowledge about menopause phenomenon. Majority of respondents had positive (72.4%) attitude towards menopause and 27.6% had negative attitude towards menopause. Conclusion: Majority of women in the current study had moderate knowledge about menopause. Women's attitude towards menopause in majority of women was positive and they perceived menopause as a natural event and not a disease. The study reflects that the respondents widely varied in their ideas about the mean age of menopause as well as about the impact of menopause on their routine life. Key Words: Menopause, knowledge, attitude, Pakistan.